2005
DOI: 10.1517/14712598.5.7.893
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous morphine: opening new doors for the treatment of pain and addiction

Abstract: Nitric oxide (NO) signalling is at the forefront of intense research interest because its many effects remain controversial and seemingly contradictory. This paper examines its role as a potential mediator of pain and tolerance. Within this context discussion covers endogenous morphine, documenting its ability to be made in animal tissues, including nervous tissue, and in diverse animal phyla. Supporting morphine as an endogenous signalling molecule is the presence of the newly cloned mu3 opiate receptor subty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Year Published

2006
2006
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 109 publications
0
16
0
3
Order By: Relevance
“…In this regard we are drawn to nitric oxide (NO) signaling because of its uniform presence in living organisms and its coupling to morphine signaling (28,(32)(33)(34). Initially, it was demonstrated that vascular dilation is mediated to a large extent by endothelium-dependent NO, produced by the enzyme nitric oxide synthase (NOS) in the presence of the cofactor tetrahydrobiopterin (BH4), found only in animals, as well as mediated via the cGMP-dependent downstream signaling cascade (35)(36)(37)(38)(39), found in both plants and animals.…”
Section: Intracellular Signalingmentioning
confidence: 99%
“…In this regard we are drawn to nitric oxide (NO) signaling because of its uniform presence in living organisms and its coupling to morphine signaling (28,(32)(33)(34). Initially, it was demonstrated that vascular dilation is mediated to a large extent by endothelium-dependent NO, produced by the enzyme nitric oxide synthase (NOS) in the presence of the cofactor tetrahydrobiopterin (BH4), found only in animals, as well as mediated via the cGMP-dependent downstream signaling cascade (35)(36)(37)(38)(39), found in both plants and animals.…”
Section: Intracellular Signalingmentioning
confidence: 99%
“…Dopamine and NO are important neurotransmitters. Many previous studies showed that their abnormality was concerned with morphine dependence and tolerance [19][20][21][22] . As GTP is the precursor of BH4, excessive catabolism and insufficient anabolism of purine nucleotides by morphine administration may cause serious subsequent effects in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, cortisol and norepinephrine are primarily responsible (61)(62)(63)(64)(65). Other molecules involved, e.g., melatonin (66) and anandamide (28), and the connection of NO with the pain response (16,28,65,66), as mentioned above, have also been detected.…”
Section: Pain Perception As a Homeostatic Mechanism And The Relaxatiomentioning
confidence: 92%
“…This information can further be used to understand some of the endogenous pain relief that occurs particularly after exposure to a series of painful stimuli, a mechanism that is found to have morphine-like properties and, perhaps, is mediated via these endocannabinoid and morphine-laden amygdalar pathways (14,16). Further credence to these findings stems from lesional data.…”
Section: Specific Neural Pathways Involved In Pain Processingmentioning
confidence: 99%
See 1 more Smart Citation